2022
DOI: 10.1177/10105395221139347
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Microbial Evaluation of Dental Caries Status and Associated Factors Among Primary Schoolchildren in Myanmar: A Cross-Sectional Study

Abstract: The study aimed to investigate the prevalence and associated factors of dental caries on primary teeth and to evaluate the cariogenic bacteria in dental plaque and saliva among Myanmar schoolchildren. A cross-sectional study was undertaken among 264 schoolchildren from three primary schools in the urban area of Yangon city in 2019. Clinical oral examinations, caries risk tests, and questionnaire surveys were conducted. Overall caries prevalence was 84.1% with a mean decayed, missing, filled primary teeth (dmft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 24 publications
2
4
0
Order By: Relevance
“…The results of this study provide the updated prevalence of ECC and associated factors among five-year-old children in Mandalay, Myanmar, which could be used to develop oral health prevention and promotion strategies for this age group. The results of this study showed similar caries and dmft prevalence rates to those reported in the Myanmar National Oral Health Survey (84.1% and 5.71) ( 20 , 21 ) and in other studies conducted in different cities including in Naypyidaw (81.3%, 4.26 ± 3.76) ( 22 ) and Yangon (84.1%, 5.84 ± 4.57) ( 19 ). These findings demonstrated that ECC prevalence remains high and severe among young Myanmar children.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The results of this study provide the updated prevalence of ECC and associated factors among five-year-old children in Mandalay, Myanmar, which could be used to develop oral health prevention and promotion strategies for this age group. The results of this study showed similar caries and dmft prevalence rates to those reported in the Myanmar National Oral Health Survey (84.1% and 5.71) ( 20 , 21 ) and in other studies conducted in different cities including in Naypyidaw (81.3%, 4.26 ± 3.76) ( 22 ) and Yangon (84.1%, 5.84 ± 4.57) ( 19 ). These findings demonstrated that ECC prevalence remains high and severe among young Myanmar children.…”
Section: Discussionsupporting
confidence: 88%
“…According to the systematic review conducted in Southeast Asia countries, children aged five to six years had a particularly high prevalence (25%-95%) of ECC (17). The Republic of the Union of Myanmar, a Southeast Asia country with a population of approximately 54 million people, is among the country where ECC is highly prevalent among young children (18)(19)(20)(21). According to the National Oral Health survey (2016-2017), the mean dmft of 6-year-old-school children was 5.7 whereas the prevalence of untreated caries was 84.1% (20,21).…”
mentioning
confidence: 99%
“…Xuan et al (2017) concluded that the CAT (using Cariostat (Sankin)) could be employed to predict the caries risk of 3-year-old caries-free children. Thwin et al (2022) used CAT scores to investigate the anti-caries effects of a school-administered fluoride varnish. CAT scores have also been employed to identify risk factors for caries in enamel and dentin in adolescents (Wang et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…This study showed the caries experience was high and comparable with previous Myanmar studies. 1,2,5 Childhood caries was shown to be family-dependent and later-born children were an increased possibility of caries development. Therefore, there is a need to create supportive family environments and also give parental attention to their later-born child.…”
Section: Discussionmentioning
confidence: 99%
“…Early childhood caries (ECC), a serious public health problem, is severe and prevalent in Myanmar children. 1,2 ECC has significant influences on individuals, families, and societies, and links with other frequent diseases of childhood, primarily due to risk factors shared with other noncommunicable diseases. 3 Maternal factors such as mother's education and oral health literacy are likely to influence child's oral health.…”
Section: Introductionmentioning
confidence: 99%